The Effectiveness of Applying Google Classroom to Student Learning Outcomes - Farida, Ida; Thomasson, Aquinas (CV. Rayyan Dwi Bharata, 2022)
In the midst of a very broad development of globalization among today’s society, technological developments have made technological developments. Therefore, with the density of technological developments as it is today, it creates a lot of applications that can be used for activities in the learning process, for example, such as Google Meet, Zoom, Kahoot, Quizz, Google Class. The main problem in this study is whether the application of Google Classroom learning applications on learning outcomes in class XI students of SMAN 1 CIKANDE. This study aims to describe and explain the effectiveness of learning by applying the Google Classroom learning application to the learning outcomes of class XI students of SMAN 1 CIKANDE. This type of resear ch is through a Quantitative Survey approach or questionnaire. The results of descriptive analysis show that the achievement of student learning outcomes can be seen Regarding the Google Classroom Learning Application Making it Easy for Students in Learning Category Agree obtained a percentage of 56%, while for Learning Outcomes More Effective Using the Google Classroom Application, Category Agree to obtain a percentage of 66%. Based on this description, the effectiveness of the use of the Google classroom learning application on the learning outcomes of class XI students at SMAN 1 Cikande is said to be successful.